2013
DOI: 10.1016/j.str.2013.06.012
|View full text |Cite
|
Sign up to set email alerts
|

The Cardiac Ryanodine Receptor N-Terminal Region Contains an Anion Binding Site that Is Targeted by Disease Mutations

Abstract: Ryanodine receptors (RyRs) are calcium release channels located in the membrane of the endoplasmic and sarcoplasmic reticulum and play a major role in muscle excitation-contraction coupling. The cardiac isoform (RyR2) is the target for >150 mutations that cause catecholaminergic polymorphic ventricular tachycardia (CPVT) and other conditions. Here, we present the crystal structure of the N-terminal region of RyR2 (1-547), an area encompassing 29 distinct disease mutations. The protein folds up in three individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 41 publications
3
73
0
Order By: Relevance
“…However, how the NH 2 -terminal region regulates the activation and termination of Ca 2ϩ release and how mutations in this region impair these processes are unclear. The NH 2 -terminal region of RyR2 encompasses three well defined domains: domain A (residues 1-217), domain B (residues 218 -409), and domain C (residues 410 -543) (9,13). In the present study, we assessed the role of these individual domains in Ca 2ϩ release activation and termination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, how the NH 2 -terminal region regulates the activation and termination of Ca 2ϩ release and how mutations in this region impair these processes are unclear. The NH 2 -terminal region of RyR2 encompasses three well defined domains: domain A (residues 1-217), domain B (residues 218 -409), and domain C (residues 410 -543) (9,13). In the present study, we assessed the role of these individual domains in Ca 2ϩ release activation and termination.…”
Section: Discussionmentioning
confidence: 99%
“…The intra-and intersubunit interactions between domains A and B are believed to be important for stabilizing the closed state of the channel. Disease mutations located in interfaces between domains A and B would weaken these interactions, thus facilitating channel opening (7)(8)(9)(10)(11)(12)(13)(14). Del-A would be expected to remove both intra-and intersubunit interactions between domains A and B, leading to destabilization of the closed state and channel activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the 420 site seems to be important for the RyR 2 function. Structural analyses have shown that this residue highly conserved among species plays an important role in the channel conformation (45,46). The RyR 2 R420Q loses the capacity to bind Cl -, which maintains the three regions of the N terminal domain in place (45), although the functional consequences remained to be elucidated.…”
Section: R420qmentioning
confidence: 99%
“…The p.(Arg420Gln) mutation lies within the N terminal region. Kimlicka et al have shown that this mutation results in the loss of chloride binding and removal of links between two domains of RyR2, domain A and domain B [8]. This in turn results in alterations in the domain orientations.…”
Section: Discussionmentioning
confidence: 99%